2020
DOI: 10.1038/s41598-020-68375-7
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic fibrin clot properties associated with NETs formation characterize acute pulmonary embolism patients with higher mortality risk

Abstract: Venous thromboembolism is associated with formation of denser fibrin clots resistant to lysis. We investigated whether prothrombotic plasma clot properties are associated with the severity of acute pulmonary embolism (PE). We enrolled 126 normotensive acute PE patients (aged 58 ± 14 years) and 25 age- and sex-matched healthy controls. Plasma fibrin clot permeability (K s ), clot lysis time (CLT), endogenous thrombin potential (ETP), plasminogen activator inhibitor-1 (PAI-1), and citrulli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Recently, we have shown that prothrombotic fibrin clot phenotype, including reduced clot permeability and prolonged CLT, was associated with higher early mortality risk and enhanced neutrophil extracellular trap formation in acute PE patients. 14 Moreover, we found that prolonged CLT assessed on admission in PE patients could be helpful in identifying intermediate-risk PE patients at increased risk of death. 14 Elevated lactate has been found to contribute to both unfavorably modified fibrin clot characteristics in acute PE patients.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Recently, we have shown that prothrombotic fibrin clot phenotype, including reduced clot permeability and prolonged CLT, was associated with higher early mortality risk and enhanced neutrophil extracellular trap formation in acute PE patients. 14 Moreover, we found that prolonged CLT assessed on admission in PE patients could be helpful in identifying intermediate-risk PE patients at increased risk of death. 14 Elevated lactate has been found to contribute to both unfavorably modified fibrin clot characteristics in acute PE patients.…”
Section: Introductionmentioning
confidence: 84%
“…14 Moreover, we found that prolonged CLT assessed on admission in PE patients could be helpful in identifying intermediate-risk PE patients at increased risk of death. 14 Elevated lactate has been found to contribute to both unfavorably modified fibrin clot characteristics in acute PE patients. 15 Based on analysis of thromboemboli retrieved from patients with PE during embolectomy, more tightly packed fibrin fibers have been shown in segmental pulmonary arteries compared with those removed from lobar branches, suggesting that the fibrin architecture can reflect embolus resistance to fibrinolysis.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Fibrin clots enriched in histone-DNA complexes had higher stability, rigidity, and prolonged clot lysis time [14]. NETs have been shown to increase in vitro thrombin generation in septic patients' blood [15]. As far as we know, there are no reports showing whether lactate concentrations in acute PE patients are linked to the prothrombotic changes in circulating blood.…”
Section: Introductionmentioning
confidence: 99%